A Comparative Study of Koelreuteria paniculata Laxm. Aerial Parts Essential Oil Composition. Issue 6 (1st November 2020) - Andonova, Tsvetelina; Dimitrova-Dyulgerova, Ivanka; Slavov, Iliya; Muhovski, Yordan; Stoyanova, Albena
Abstract: Volatiles from aerial parts of Koelreuteria paniculata Laxm. have been isolated by hydro-distillation for the first time and they were identified by GC/MS analysis. The yield of essential oils was 0.035 %, 0.021 %, 0.018 %, 0.011 % in the flower buds, flowers, leaves and stem bark, respectively. The main essential oil constituents of the flower buds (over 3.0 %) were eleven: linoleic acid (14.98 %), palmitic acid (12.72 %), linolenic acid (7.03 %), n-pentacosane (6.15 %), (Z, Z)-farnesyl acetone (5.52 %), (Z)-nerolidol (4.15 %), n-heptacosane (3.71 %), methyl octadecanoate (3.36 %), oleic acid (3.31 %), methyl tetradecanoate (3.25 %) and ethyl hexadecanoate (3.04 %). There were twelve major compounds of the flower essential oil: (Z, Z)-farnesyl acetone (17.3 %), isopropyl tetradecanoate (6.05 %), n-pentacosane (5.86 %), palmitic acid (5.64 %), n-heptacosane (4.79 %), ethyl tetradecanoate (4.37 %), Z-nerolidol (4.35 %), ethyl dodecanoate (4.22 %), ethyl-hexadecanoate (3.9 %), linoleic acid (3.03 %), lauric acid (3.19 %) and n-nonacosane (3.34 %). In the bark essential oil, ten compounds were over 3 %: drimenol (16.19 %), n-pentacosane (10.54 %), (E, E)-α-farnesene (9.49 %), n-heptacosane (6.77 %), (Z, Z)-farnesyl acetone (5.08 %), n-nonacosane (5.04 %), ethyl hexadecanoate (4.07 %), ethyl dodecanoate (3.53 %) and palmitic acid (3.2 %). In the leaf essential oil, the main components were six: (E, E)-α-farnesene (37.90 %), α-copaen-11-ol (8.89 %), (E)-β-farnesene (6.92 %), nerolidol (7.60 % - cis- and trans- ) and isophytol (6.14 %). The composition of K. paniculata essential oils showed that they can be a potential natural source for food, cosmetics and pharmaceuticals.